"It's Like Youth are Talking Into a Microphone That is not Plugged in": Engaging Youth in Disaster Risk Reduction Through Photovoice. (December 2022) - Pickering, Christina J.; Al-Baldawi, Zobaida; McVean, Lauren; Amany, Raissa A.; Adan, Munira; Baker, Lucy; Al-Baldawi, Zaynab; L. O'Sullivan, Tracey
Over the last decade, youth have been acknowledged as agents of change in the fight against climate change, and more recently in disaster risk reduction. However, there is a need for improved opportunities for youth to participate and have their voices heard in both contexts. Our Photovoice study explores youth perceptions of the capability of youth to participate in disaster risk reduction and climate change action. We conducted six focus groups from February 2019 to June 2019 with four teenaged youth participants in Ottawa, Canada, hosting two virtual Photovoice exhibitions in 2021. Our results highlight 11 themes across a variety of topics including youth as assets, youth-adult partnerships, political action on consumerism, social media, education, accessibility, and art as knowledge translation. We provide four calls to action, centering youth participation and leadership across all of them, to guide stakeholders in how to improve disaster risk reduction and climate change initiatives by meaningfully including youth as stakeholders.